2021
DOI: 10.1111/gcb.15718
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene‐regulated leaf lifespan explains divergent responses of plant productivity to warming among three hydrologically different growing seasons

Abstract: Leaf senescence is known to be regulated by the plant hormone ethylene, but how leaf lifespan responds to global environmental change and links to ecosystem‐level responses remains largely unexplored. Here we investigated the effects of climate warming and nitrogen addition on plant functional traits, plant hormone ethylene and net primary production in a 13‐year field experiment in a desert steppe. Across the last 3 years of the experiment (2016–2018), plant productivity increased under warming only in 2016, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 56 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…We found that warming significantly increased foliar δ 15 N (Figure 4), indicating warming increases the fractionation of δ 15 N and exacerbates the loss of lighter 14 N in the soil. Likewise, warming treatments triggered large N losses in desert steppes and subarctic ecosystems (Maranon-Jimenez et al, 2019;Ren et al, 2021). Moreover, δ 15 N fractionation was intensified by lower rainfall, as evidenced by the significant negative correlation between seasonal rainfall and the response ratio of foliar δ 15 N to warming.…”
Section: Mechanisms Of Stoichiometry To Growth Under Warmingmentioning
confidence: 95%
See 1 more Smart Citation
“…We found that warming significantly increased foliar δ 15 N (Figure 4), indicating warming increases the fractionation of δ 15 N and exacerbates the loss of lighter 14 N in the soil. Likewise, warming treatments triggered large N losses in desert steppes and subarctic ecosystems (Maranon-Jimenez et al, 2019;Ren et al, 2021). Moreover, δ 15 N fractionation was intensified by lower rainfall, as evidenced by the significant negative correlation between seasonal rainfall and the response ratio of foliar δ 15 N to warming.…”
Section: Mechanisms Of Stoichiometry To Growth Under Warmingmentioning
confidence: 95%
“…Many other factors, such as rainfall, developmental stage, and resource supply might also affect the response of plant stoichiometry to warming (Han et al, 2011). One-time sampling only provides a "snapshot" of the plant's response to warming, and the details of seasonal and interannual variations in these responses warrant further investigation (Ren et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Ethephon is a precursor of ethylene synthesis and signal transduction, and it functions as a plant growth regulator. Depending on the environment, ethylene signaling pathways can lead to the inhibition or activation of a series of genes, thereby inducing differential morphological developments in plants [17,18]. In contrast, CoCl 2 promotes the synthesis of auxin and cytokinin and directly inhibits the synthesis of ethylene; therefore, it can reduce the effects of ethylene, and thus, significantly affect plant growth and development as well as the stress resistance physiology [19].…”
Section: Experimental Designmentioning
confidence: 99%
“…Under P stress conditions, low concentrations of CoCl 2 promoted both POD and SOD activities in Chinese fir seedlings [ 17 ]. The application of CoCl 2 in desert grasslands can extend the life span of plant leaves by reducing ethylene content [ 18 ]. Therefore, under Pi deficiency, we used ethephon and CoCl 2 to control the exogenous ethylene content separately to observe its response in the genes.…”
Section: Introductionmentioning
confidence: 99%